Color Alteration of Resin Composites by Cigarette Smoke with Various Levels of Tar, Nicotine, and Carbon Monoxide - Jéssica Dias Theobaldo; Waldemir Francisco Vieira-Junior; Marcela Alvarez Ferretti; Lorena Barros Costa; Giselle Maria Marchi; Debora Alves Nunes Leite Lima; Flávio Henrique Baggio Aguiar (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To evaluate the effect of various types of cigarettes on the color of microhybrid (MH) and nanofilled (NF) resin composites. Material and Methods: Disc-shaped specimens (5 × 2 mm; n = 10) of MH (Filtek Z250, 3M) or NF (Filtek Z350XT, 3M) were exposed or not (control) to cigarette smoke (20 cigarettes daily × 5 days) from four commercial cigarettes with increasing concentrations of tar, nicotine, and carbon monoxide (MSL < MFP < MBI < MR). The cigarettes had an additional filter (MFP) or added flavoring (MBI). The color parameters (L*, a*, b*, ΔEab,ΔE00) were determined considering baseline versus after exposure to cigarette smoke. Data were submitted to Mann-Whitney, Kruskal-Wallis, and Dunn tests (α=0.05). Results: Significant differences were observed for ΔL* (toward black), Δa* (toward red), ΔEab, and ΔE00 of both resin composites compared with the control (p<0.05) regardless of the type of cigarette, with higher values for NF (p<0.05). For the MH, MBI provided higher negative Δ L* variation compared to MSL and MR (p<0.05). For the NF, higher Δa* values were observed for MR and MSL, with significant differences from MFP and MBI (p<0.05). Regardless of the cigarette, ΔEab and ΔE00 exceeded the limits of perceptibility and acceptability of color alteration. Conclusion: Color alteration of resin composites was modulated by the cigarette and resin composite type, the NF resin composite being more susceptible to staining.